What it takes to be a manager: The case of Malaysian five-star resort hotels - Ahmad, Rozila; Zainol, Noor Azimin (2011)
This article investigates the requirement for managerial posts in five-star resort hotels in Malaysia. Despite the growth of hotel industry in Malaysia, academic literature especially qualitative empirical study focusing on the human capital needs of the industry in the country is scarce. Different from other industries, in the hotel industry a Bachelor’s Degree hardly guarantees the attainment of management position. Based on interviews with 42 hotel employees including 19 managers from six hotels, this article suggests that work experience and leadership skill is crucial for hotel managers to perform their job. Other requirements are knowledge,education and English proficiency. This suggestion is supported by the employees’ profile. The implications are discussed, emphasizing the need to consider increasing hotel students’ work experience in the industry and enhancing their leadership skill.